Enteropathogenic Infections: Organoids Go Bacterial. (8th January 2021) - Hentschel, Viktoria; Arnold, Frank; Seufferlein, Thomas; Azoitei, Ninel; Kleger, Alexander; Müller, Martin
Abstract : Enteric infections represent a major health care challenge which is particularly prevalent in countries with restricted access to clean water and sanitation and lacking personal hygiene precautions, altogether facilitating fecal-oral transmission of a heterogeneous spectrum of enteropathogenic microorganisms. Among these, bacterial species are responsible for a considerable proportion of illnesses, hospitalizations, and fatal cases, all of which have been continuously contributing to ignite researchers' interest in further exploring their individual pathogenicity. Beyond the universally accepted animal models, intestinal organoids are increasingly valued for their ability to mimic key architectural and physiologic features of the native intestinal mucosa. As a consequence, they are regarded as the most versatile and naturalistic in vitro model of the gut, allowing monitoring of adherence, invasion, intracellular trafficking, and propagation as well as repurposing components of the host cell equipment. At the same time, infected intestinal organoids allow close characterization of the host epithelium's immune response to enteropathogens. In this review, (i) we provide a profound update on intestinal organoid-based tissue engineering, (ii) we report the latest pathophysiological findings defining the infected intestinal organoids, and (iii) we discuss the advantages and limitations of this in vitro model.